Of xenophobia and citizenship: the politics of exclusion and inclusion in Africa - (:unkn) unknown (My University, 2015)
Recent literature on the continent has focused attention on the increasing numberof forms of belonging using different labels: autochthony, nativism, indigeneity,ethnicity, and in some cases xenophobia. The latter term generally refers to discoursesand practices that are discriminatory towards foreign nationals, butWimmer (1997) also sheds light on the existence of deeper political struggles forthe collective goods of the state and the building of structures of legitimacy inaccessing those goods. In many instances, those structures are based on collectiveidentities and real or fantasized notions of national community (Wimmer 1997:32). In the African contexts, decolonization struggles have specifically shapedthe type of nation-building enterprises that have emerged in the postcolonialperiod (Chipkin 2007). Taking into consideration both this broader theoreticaldimension and the specific historical trajectories of nationalist discourses in theAfrican contexts, our understanding of xenophobia as discussed in this issue consistsof the systematic situated (in one institution) or cross-cutting constructionthat sees strangers as a threat to society, justifying their exclusion and, at times,their suppression...
Keywords: African Research